Carbon quantum dots in bioimaging and biomedicines - Das, Surya; Mondal, Somnath; Ghosh, Dhiman (Frontiers in Bioengineering and Biotechnology, 2024)
Carbon quantum dots (CQDs) are gaining a lot more attention than traditional semiconductor quantum dots owing to their intrinsic fluorescence property, chemical inertness, biocompatibility, non-toxicity, and simple and inexpensive synthetic route of preparation. These properties allow CQDs to be utilized for a broad range of applications in various fields of scientific research including biomedical sciences, particularly in bioimaging and biomedicines. CQDs are a promising choice for advanced nanomaterials research for bioimaging and biomedicines owing to their unique chemical, physical, and optical properties. CQDs doped with hetero atom, or polymer composite materials are extremely advantageous for biochemical, biological, and biomedical applications since they are easy to prepare, biocompatible, and have beneficial properties. This type of CQD is highly useful in phototherapy, gene therapy, medication delivery, and bioimaging. This review explores the applications of CQDs in bioimaging and biomedicine, highlighting recent advancements and future possibilities to increase interest in their numerous advantages for therapeutic applications.